2018
DOI: 10.3727/096504017x14965111926391
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Carbonic Anhydrase IX by Ureidosulfonamide Inhibitor U104 Reduces Prostate Cancer Cell Growth, But Does Not Modulate Daunorubicin or Cisplatin Cytotoxicity

Abstract: Carbonic anhydrase (CA) IX has emerged as a promising target for cancer therapy. It is highly upregulated in hypoxic regions and mediates pH regulation critical for tumor cell survival as well as extracellular acidification of the tumor microenvironment, which promotes tumor aggressiveness via various mechanisms, such as augmenting metastatic potential. Therefore, the aim of this study was to analyze the complex interdependency between CA IX and the tumor microenvironment in prostate tumor cells with regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…The decreased pHi may be responsible for the decreased proliferation and increased apoptosis rate (16,28). This study of rat prostate cancer cells confirmed the intracellular acidification, anti-proliferative and pro-apoptotic effects of CAIX inhibition with CAI U104 (29). In addition, recently, our previous results confirmed CAI-induced apoptosis for betulinyl sulfamates in MDA-MB-231 and MCF7 cells using different methods (21,40).…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 72%
See 1 more Smart Citation
“…The decreased pHi may be responsible for the decreased proliferation and increased apoptosis rate (16,28). This study of rat prostate cancer cells confirmed the intracellular acidification, anti-proliferative and pro-apoptotic effects of CAIX inhibition with CAI U104 (29). In addition, recently, our previous results confirmed CAI-induced apoptosis for betulinyl sulfamates in MDA-MB-231 and MCF7 cells using different methods (21,40).…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 72%
“…1). Recently, we detected similar effects in AT1 prostate cancer cells (29). In contrast to our investigations, Tang et al observed a decrease in CA9 mRNA level in MCF-7 cells after incubation with lactic acid under hypoxic conditions (30).…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 67%
“…However, to prevent intracellular H þ accumulation cancer cells upregulates proton exchangers that extrude protons in excess contributing to acidify extracellular tumour microenvironment 9,11,12 . Among these proton exchangers, a primary role is played by CA IX, an enzyme overexpressed in many types of cancers, including prostate cancer, with the potential to represent both a promising tumour biomarker and a specific target for future cancer therapies 13,[30][31][32][33][37][38][39][40][41]44 . Under the pressure of the acidic microenvironment, CA IX expression and activity are upregulated in both tumour cells 30,44 and the exosomes released extracellularly 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CA IX is overexpressed in a large number of solid tumours, whereas its expression in normal tissues is quite limited, suggesting its role as valuable tumour biomarker. Furthermore, CA IX has been validated as a target of new therapies against hypoxic tumours with one sulphonamide inhibitor (SLC-0111) in Phase Ib/II clinical trials 13,30,37-39(p20), [40][41][42] . Indeed CA IX is the most widely expressed gene in response to hypoxia, playing a pivotal role in tumour pH regulation 13,30,37,41 ; thus conferring to cancer cells a survival advantage in hypoxic and acidic microenvironments 43 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation